Genotypes exhibit no variation in precision foraging in mycorrhizal Norway spruce seedlings. - Velmala, Sannakajsa; Salmela, Matti; Chan, Tommy; Hölttä, Teemu; Hamberg, Leena; Sievänen, Risto; Pennanen, Taina (Springer Nature, 2022)
Aims Fine roots, that comprise the adjustable part of the root system, are important in spatially heterogeneous boreal forest soils. We investigated the soil exploring patterns of Norway spruce (Picea abies) seedlings of equal height belonging to families representing two contrasting growth phenotypes that have shown fast and slow growth rates in long-term experiments. We hypothesised that seedlings of the fast-growing phenotype would show a more explorative root growth strategy, intense branching, and root proliferation in response to the nutrient patch, and that slow-growing phenotypes would be more tolerant to drought stress. Methods Seedlings were grown in flat Perspex microcosms with a clod of humus placed in the mid-bottom part of each microcosm for eight months. The order-based and functional classification, branching topology, and size of seedling root systems were studied with WinRHIZO™ image-analysis software and root exploration patterns with LIGNUM-model simulations. In addition, transpiration, stomatal conductance, net assimilation rate responses were measured. Results No differences were found in the early foraging of roots for the humus clod nor net assimilation rate and transpiration between the phenotype groups. Seedlings were favouring exploitation over exploration in the early phases of development regardless of growth phenotype group. However, in fast-growing phenotypes, the main roots were longer, and the lateral root pool favoured long and bifurcated laterals that formed larger absorptive root area. Conclusions Our results indicate that in nutrient-poor conditions, better growth of lateral roots precedes future differences in the aboveground growth rate of Norway spruce.
Keywords: root architecture; lateral root; convex hull; intraspecific variation; root exploitation; Norway spruce